PENERAPAN METODE PENGAKUAN PENDAPATAN TERHADAP KEWAJARAN LAPORAN KEUANGAN PADA BD MOTOR - Zulkarnain Moeshak Zen (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2015)
Recognition needs to be done at the right moment on the economic events generated revenue, as well as the amount recognized should be measured precisely and surely that doesn’t result in misinformation presented and decision making. This research aimed to find out whether the revenue recognition and measurement at BD Motor was adjusted with PSAK No.23, so the financial statement presentation of BD Motor will be adjusted with generally accepted accounting standard in Indonesia. The research method uses descriptive study with primary and secondary data. The research result is show that the revenue recognition and measurement at BD Motor was adjusted under Financial Statement Accounting Standard No.23. where the company recognition revenue used accrual basis method, that the revenue recognized when the service sales transactions happened. Recognition of the company's revenue has been referred to in PSAK No. 23 seen from the value of service sales are recorded as revenue can be estimated with certainty and likely to be realized. Revenue measurement used historical measurement basic based on fair value exchange that received or will be received in cash or cash equivalent.